Association of Cardiac Arrest With Opioid Overdose in Transport. (June 2022) - Ritter, Marissa L; Bohr, Adam D; McQueen, Matthew B
Introduction: Drug overdose is the leading cause of injury-related death in the United States. It has been linked to respiratory depression and cardiac toxicity, both of which can lead to cardiac arrest. Despite this potential association, few studies have examined this relationship, particularly in transport to the hospital. The purpose of this research was to determine if there was a relationship between opioid overdose and cardiac arrest in transport. Methods: A sample (n = 1 000 000) was utilized from the National EMS Information System (NEMSIS) from the year 2019. A logistic regression model was used to predict cardiac arrest from dispatch reason with gender, race, and age included as controls. Results: Overdose-related dispatch reason was associated with an increased likelihood of cardiac arrest in transport (Odds Ratio = 1.65, 95% Confidence Interval: [1.22, 2.22]). Conclusions: Opioid overdose is associated with an increased incidence of cardiac arrest in transport in the United States.